Time-dependent seismic hazard in mining. - Finnie, Gerard John. (My University, 1993)
A strategy to determine the probability that a mining induced seismic event will occur with magnitude which exceeds some specified value within a given time is investigated. The model allows for a non-linear frequency-magnitude relationship and a Poissonian distribution of seismic events in time. The procedure is also independent of the method of mining and of the mining geometry. The model was applied to clusters of various sizes) starting from small areas on a single reef and ending up with the entire mine as a single entity. It was shown that the model works well with large populations of events, but to be successful with small clusters, the retention of the Poisson distribution is too restrictive and a non-stationary model of seismicevent occurrence in time will have to be developed.
A project report submitted to the Faculty of Mining Engineering, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering.
Keywords: Seismology -- Mathematical models.